The State and Prospects of Winemaking in Poland - Assessment of Conditions in The Regional Aspect on The Example of The Lubusz Voivodeship - Piotr KUŁYK; Mariola MICHAŁOWSKA (Communications of International Proceedings, 2023)
The article presents the state and prospects of winemaking in Poland, with particular emphasis on the Lubusz Voivodeship. The aim of the study was to identify the most important conditions favoring the development of winemaking in the Lubusz region, based on a list of strengths, weaknesses and an assessment of market opportunities and threats, as well as the most important implications for the further development of Lubusz winemaking. In addition, a diagnosis of the state of winemaking in Poland was presented, broken down into individual voivodeships in terms of the number of wine producers. In the research procedure, the authors used literature analysis, data from  the National Support Centre for Agriculture (KOWR) and the results of a survey conducted among young consumers from the Lubusz Voivodeship. The survey was addressed to 437 respondents from the Lubuskie Voivodeship, aged 18-35. They were carried out between October and December 2020. In the light of the presented research, it can be seen that winemaking in Poland is developing, but for further growth to occur, promotion is important, i.e. a number of different activities aimed at promoting wine events. Activities should be aimed at cooperation among winemakers. The research results can be treated as a premise for developing a strategy for the development of winemaking in the Lubusz Voivodeship, indicating the most important conditions supporting the development of the regional wine market. It should be noted that this issue has not been sufficiently examined in the context of regional conditions on the example of the Lubuskie Voivodeship. Therefore, it is important to learn about the opportunities and barriers to the development of Lubusz winemaking. The research provides the basis for proposing a strategy for Lubusz winemaking, based on a conservative strategy.
Keywords: viticulture; regional wine; winemaking in Poland; Lubusz Voivodeship